2008
DOI: 10.1097/aln.0b013e318182a4a3
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Continuous Posterior Lumbar Plexus Nerve Blocks after Hip Arthroplasty

Abstract: Background-The authors tested the hypotheses that after hip arthroplasty, ambulation distance is increased and the time required to reach three specific readiness-for-discharge criteria is shorter with a 4-day ambulatory continuous lumbar plexus block (cLPB) than with an overnight cLPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 34 publications
1
82
0
1
Order By: Relevance
“…Early ambulation after TKA has been shown to help decrease deep venous thrombosis of the legs, enhance muscle strength and gait control, and decrease hospital LOS [21,30]. Although the analgesic benefits of CPNB in the setting of joint arthroplasty have been shown previously, clinical studies demonstrate that perineural local anesthetic infusions exert varying degrees of analgesia and motor block at different anatomic sites [11,12,14,15,17]. Recent studies of femoral nerve and lumbar plexus catheters have shown that typical perineural local anesthetic infusion doses produce clinically significant quadriceps weakness when administered via catheters inserted using conventional techniques [3,6,16].…”
Section: Discussionmentioning
confidence: 99%
“…Early ambulation after TKA has been shown to help decrease deep venous thrombosis of the legs, enhance muscle strength and gait control, and decrease hospital LOS [21,30]. Although the analgesic benefits of CPNB in the setting of joint arthroplasty have been shown previously, clinical studies demonstrate that perineural local anesthetic infusions exert varying degrees of analgesia and motor block at different anatomic sites [11,12,14,15,17]. Recent studies of femoral nerve and lumbar plexus catheters have shown that typical perineural local anesthetic infusion doses produce clinically significant quadriceps weakness when administered via catheters inserted using conventional techniques [3,6,16].…”
Section: Discussionmentioning
confidence: 99%
“…Wegener and colleagues 24 Ilfeld and colleagues 21 Ilfeld and colleagues 22 Ilfeld and colleagues 20 Ilfeld and colleagues 3 Ilfeld and colleagues 5 Williams and colleagues postoperative day 2 linked the falls to a violation of postoperative safety instruction and ambulation without supervision. 24 After repeated patient and nursing education about peripheral nerve block-induced muscle weakness and the risk of falling, no subsequent falls occurred within the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Some data suggest that a 4-d continuous lumbar plexus block may be compatible with successful postoperative ambulation. Recent studies did not have enough power though, to show statistical significant superiority compared to overnight use [21] . Further, it has to be noted that under peripheral nerve block, for example a continuous lumbar plexus block, the risk of postoperative falls seems to be increased compared to non-continuous or no block used in patients with major lower extremity orthopedic surgery.…”
Section: Benefits and Pitfallsmentioning
confidence: 99%